Grid impact analysis and interval forecasting of solar PV generation - Verma, Jatin (2019)
Solar PV is renowned all around the world, but its prevalence varies with a country’s solar profile. Singapore is an island country which has solar energy as the only promising renewable energy option. On the UN’s request to submit the Intended Nationally Determined Contribution (INDC) against carbon emissions, Singapore, as a promoter of efficient energy, has come up with an elaborate Climate Action Plan towards carbon emission reduction. An aspiring leap by Singapore towards 350MWp PV capacity by 2020 is on trial, which would involve numerous PV installation projects.